Mouse Models for Atopic Dermatitis - Sakamoto, Keiko; Nagao, Keisuke (Current protocols, 2023)
Atopic dermatitis (AD) is a multifactorial disease with underlying barrier disruption and altered microbial flora, resulting in dry skin and eczematous inflammation with persistent pruritis. Mouse models have been heavily used to investigate AD pathophysiology. Among various AD mouse models, AD-like inflammation induced by topical calcipotriol, a vitamin D3 analog referred to as MC903 in experimental settings, is a versatile model that can be applied to any strain of mice, which can be used for immunologic and morphologic studies. Herein, we provide basic protocols for the topical application of MC903 and approaches to assess phenotypes. After inducing AD-like inflammation, the skin is harvested for flow cytometry analysis, as well as for histologic and immunofluorescence microscopy analyses. The combination of these approaches enables accurate characterization of the degree of inflammation, type of inflammatory infiltrate, and localization of immune infiltrates. Published 2023. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1: Application of MC903 and gross phenotype assessment Basic Protocol 2: Processing skin for flow cytometry analysis Support Protocol: Skin immune cell surface staining and flow cytometry analysis Basic Protocol 3: Harvesting skin for histologic analysis Basic Protocol 4: Immunofluorescence staining to identify immune cell infiltrates.